Protective Effect of Andropraphis Paniculata Aqueous Extract (EAAp) Against Isoniazid and Rifampicin-Induced Rat Liver Damage - Risdawati Djohan; Ambar Harjanti; Pendrianto Pendrianto (Syntax Corporation Indonesia, 2023)
Isoniazid (INH) and rifampicin (RIF) are first-line antituberculosis drugs (OAT) in tuberculosis treatment that are used for at least 6 months. The use of OAT has been associated with toxic reactions in the liver and causes hepatitis. This study aimed to determine the effect of an aqueous extract of Andrographis paniculata (EAAp) on liver damage induced by INH and RIF. Method: Male Sprague-Dawley rats weighing 250–300g were divided into 5 groups, each consisting of 6 mice. Animals were given isoniazid and rifampicin at 100 mg/kg, respectively, to induce liver damage, silymarin (25 mg/kg) for the positive control group, and Ap extract at doses of 200mg and 300 mg/kg for the test group. All treatments were given orally once daily for 28 days. Measurement of serum aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), bilirubin, and liver histopathology levels was carried out to determine the effect of EAAp on liver damage by INH and RIF. Results: Rats treated with INH+RIF were hepatotoxic, as evidenced by increased serum ALT, AST, and ALP activity, total bilirubin levels, and histopathological changes in the liver. Administration of Ap extract doses of 200 mg/kg and 300 mg/kg significantly decreased liver biochemical and histological changes caused by OAT. Conclusions: EAAp has a protective effect against hepatotoxic-induced INH and RIF in animal models.